O uso de um objeto de aprendizagem na disciplina de Primeiros Socorros - Nascimento, Renato Luiz do (2011)
This dissertation is the result of a study that aims the development, implementationand validation of an educational learning object (LO), called: Accidents into bathroom. This study intended to develop through this LO the thematic of initial primary approach to the First Aids discipline in a subsequent course of radiology technician. The LO is a tool that can be described in its flexibility and reusability. It can be used as material of technological support for education. The educational activities are based in internet and local nets. From documentation to production, the study in its conception, development and validation highlighted in each step of its construction a methodology of technological production. A support technical staff was involved in the construction process of the LO. The validation was made by specialist in Nursing, Computing and Educational areas, based on objective questionnaires. A five-point Likert scale was used to analyze the instruments and measure the agreement and disagreement degree of the presented data. The study aimed to present one of the possibilities to join elements from Information and Communication Technology (ICT) to First Aids discipline contends, by considering the relationship between the development techniques of the LO and the pedagogical didactical aspects.